Combined Inositol Hexakisphosphate and Inositol Supplement Consumption Improves Serum Alpha-Amylase Activity and Hematological Parameters in Streptozotocin-Induced Type 2 Diabetic Rats - Shadae R. Foster; Lowell L. Dilworth; Jean Sparks; Ruby L. Alexander-Lindo; Felix O. Omoruyi (Advances in Pharmacological Sciences)
This study evaluated the effect of combined inositol hexakisphosphate (IP6) and inositol supplement on organ weight, intestinal ATPase activities, complete blood count, and serum analytes in streptozotocin (STZ)-induced type 2 diabetic rats. High-fat diet and a single intraperitoneal injection of streptozotocin (35 mg/kg body weight) were used to induce type 2 diabetes mellitus in Sprague–Dawley rats. The diabetic groups were then treated with either combined IP6 and inositol supplement or glibenclamide for four weeks. Organ weights, intestinal ATPase activities, complete blood count, serum α-amylase, total protein, albumin, and globulin content were determined. Pancreatic weight was significantly reduced while relative kidney and liver weights were elevated in the group treated with combined IP6 and inositol supplement compared to the nondiabetic control. Serum α-amylase activity for the glibenclamide and combination treated groups was significantly improved compared to that of the untreated diabetic group. Red cell distribution width percentage was significantly lower in the combination treated group compared to that in the untreated diabetic group, while intestinal ATPase activities were unaffected by the treatment regime. Combined IP6 and inositol supplement consumption may protect people with diabetes from increased risk of cardiovascular diseases due to the supplement's ability to maintain red cell distribution width percentage towards the normal control group.